Selection of the Best EPL Players Using AHP, PROMETHEE, and TOPSIS Methods with a Pairwise Comparison Scale - Rifqi Zulfikar; Septi Andryana; Aris Gunaryati (Institute of Computer Science (IOCS), 2020)
Every time players are assessed in terms of their performance on the field, players have the potential to compete for individual and team achievements in football, therefore a decision support system is made for the selection of the best premier league players in October 2020/2021. The 7 criteria for using the assessment include the number of goals, assists, kicks, wins, passes, fouls and plays time. In this study, there are three best player assessment methods, namely the Analytical Hierarchy Process (AHP) method, the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE), and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The use of three methods in the assessment provides a good comparison of accuracy compared to one method alone and also aims to assess concretely and accurately so that the assessment runs fairly. The making of the premier league best player selection system is programmed with PHP and uses a MySQL database that is useful for storing player data and scores.